2022
DOI: 10.1186/s13293-022-00453-z
|View full text |Cite
|
Sign up to set email alerts
|

Tendinopathy: sex bias starts from the preclinical development of tendon treatments. A systematic review

Abstract: Tendinopathies are common overuse disorders that arise both in athletes and the general population. Available tendon treatments are used both for women and men without distinction. However, the existence of a sex-based difference in tendon biology is widely demonstrated. Since basic research represents the foundation for treatment development, an equal female–male representation should be pursued in preclinical studies. This systematic review quantified the current evidence by analyzing 150 studies on 8231 ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…None of the included studies analyzed sex differences because they did not test the efficacy of the patches in both sexes simultaneously; the research groups either used only male animals ( Ide and Tokunaga, 2018 ; Chen et al, 2020 ; Chen et al, 2022 ; de Lima Santos et al, 2020 ; He et al, 2021 ; Santos et al, 2022 ) or, to a lesser extent, female animals ( Thangarajah et al, 2018 ; Credille et al, 2023 ). It is now well established that sex differences, mainly due to hormonal variations and levels, affect musculoskeletal pathologies, including tendons ( Contartese et al, 2020 ; Tschon et al, 2021 ; Mondini Trissino Da Lodi et al, 2022 ; Salamanna et al, 2022 ; Salamanna et al, 2023 ). Clinical studies involving both men and women have shown a difference in prevalence ( Razmjou et al, 2016 ; Sabo et al, 2021 ) on the extent of shoulder pathology, repair, and healing, with a higher rate of re-tear in women than in men ( Collin et al, 2015 ; Razmjou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…None of the included studies analyzed sex differences because they did not test the efficacy of the patches in both sexes simultaneously; the research groups either used only male animals ( Ide and Tokunaga, 2018 ; Chen et al, 2020 ; Chen et al, 2022 ; de Lima Santos et al, 2020 ; He et al, 2021 ; Santos et al, 2022 ) or, to a lesser extent, female animals ( Thangarajah et al, 2018 ; Credille et al, 2023 ). It is now well established that sex differences, mainly due to hormonal variations and levels, affect musculoskeletal pathologies, including tendons ( Contartese et al, 2020 ; Tschon et al, 2021 ; Mondini Trissino Da Lodi et al, 2022 ; Salamanna et al, 2022 ; Salamanna et al, 2023 ). Clinical studies involving both men and women have shown a difference in prevalence ( Razmjou et al, 2016 ; Sabo et al, 2021 ) on the extent of shoulder pathology, repair, and healing, with a higher rate of re-tear in women than in men ( Collin et al, 2015 ; Razmjou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental designs with sex bias have been recognized as an issue in both basic and translational research ( Kong et al, 2016 ; Stephenson et al, 2018 ; Villavisanis et al, 2018 ; Xiao et al, 2018 ; Coiro and Pollak, 2019 ; Plevkova et al, 2020 ; Flynn et al, 2021 ; Mercel et al, 2021 ; Mondini Trissino da Lodi et al, 2022 ; Spitschan et al, 2022 ). Even in clinical studies, the number of female participants is underrepresented substantially ( Mansukhani et al, 2016 ; Villavisanis et al, 2018 ; Feldman et al, 2019 ; Karp and Reavey, 2019 ; Burra et al, 2022 ; Mondini Trissino da Lodi et al, 2022 ). Sex or gender differences, however, exist not only in reproductive organs but also in several other characteristics, including metabolism, disease patterns and drug pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Surgery is more likely to be recommended in female athletes with ACL tears, as the female knee may be more cruciate dependent than the male knee [11]. There is a need for clinical studies to segregate sexes to assess female-specific risks and interventions in tendon and ligament injuries [12][13][14]. As such, particular efforts are needed to design specific strategies for ACL rupture prevention in female footballers to safely promote their expected growth in number and playing hours.…”
Section: Introductionmentioning
confidence: 99%